DNA barcoding of fruit flies Bactrocera occipitalis (Bezzi) and Bactrocera philippinensis Drew and Hancock (Diptera Tephritidae) from Cavite and Davao del Norte using the 5' region of the mitochondrial cytochrome C oxidase (coxI) gene) - Delomen, Michael Leonardo C. (Transactions of the National Academy of Science and Technology, 2011)
Analysis of the 5' region of the mitochondrial cytochrome oxidase gene I was done to compare the pest fruit flies Bactrocera occipitalis (Bezzi) and Bactrocera philippinensis Drew and Hancock. Adult fruit flies and larvae-infested dropped mango fruits were collected from selected orchards at Cavite and Davao del Norte. Collected adults were immediately identified while larvae from infested fruits were reared to adulthood then identified. Identification was done thru the visual analysis of six diagnostic morphological characters originally described by White and Hancock (1997) and utilized by Iwahashi (1999) to differentiate between the two species. Genomic DNA was extracted and mitochondrial cox1 gene was amplified using custom primers. PCR products were verified thru agarose gel electrophoresis and shipped to Macrogen Inc, South Korea for sequencing. Consensus sequences were derived and analyzed using the sequence analysis softwares Clustal W2 and MEGA4. The generated phylogenetic trees showed that there were no significant sequence differences between B. occipitalis and B. philippinensis. Divergence values were from zero to 0.0018%; values obtained were significantly lower than the set standard of 0.5% to establish species destination. Analysis of the 5' region of the mitochondrial cox1 gene did not show species delineation between B. occipitalis and B. philippinensis. It is recommended that further analysis be done on more samples from other locations in the Philippines.